Impact of climate change on the groundwater sustainability in the lower Chao Phraya basin, Thailand - Pinit Tanachaichoksirikun; Uma Seeboonruang; Phayom Saraphirom (My University, 2018)
This research investigates the impact of climate change on the hydraulic heads of Thailand's Lower Chao Phraya basin. The research also determines the sustainability of groundwater as the result from climate change. In the study, the climatic scenario (IPSL-CM5A-MR) of the Representative Concentration Pathways (RCP) between 2.6, 4.5 and 8.5 were considered, and the simulations were carried out using the three-dimensional groundwater flow model (i.e. MODFLOW-2000) predicting the groundwater behavior between 2017 and 2036. The findings revealed that the impact of climate change on the hydraulic head fluctuation was positively correlated. Specifically, under the IPSL-CM5A-MR RCP 4.5 that has the highest average precipitation, the average hydraulic head increased. In conclusion, the sustainability of groundwater in the Lower Chao Phraya basin was sufficient during the simulated time. However, the groundwater budget was lower than the average groundwater budget during 2009 – 2014 indicating, the groundwater storage was continuously decreased. Specifically, the 2nd, and 3rd (Phra Pradeang and Nakorn Luang) aquifers may be facing the groundwater shortage in the future.
Keywords: MODFLOW; Hydrology and Watershed Management Studies